Substitution of Concentrate with a Mixture of Moringa leaf (Moringa oleifera L.) and Cassava Pulp and Their Impact on in Vitro Fermentability and Digestability - Rahmawati, Imma; Wahyuni, Dyah; Irmawaty, Dwi Ayu Dian; Aryanti, Risca Dwi; Dhalika, Tidi; Ayuningsih, Budi; Tanuwiria, U. Hidayat; Mansyur, Mansyur; Djajuli, Mochamad; Djuned, Harun; Hernaman, Iman (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
The aim of this study was to study the use of a mixture of Moringa leaves with cassava pulp (MLCP) to replace concentrate and its impact on in vitro fermentability and digestibility. The study was conducted experimentally using a completely randomized design consisting of 5 treatments and 4 replications. Basal treatment in 40% rice straw as a source of fiber and 60% concentrate, then concentrate was replaced with MLCP in stages, namely 15%, 30%, 45%, and 60%. MCLP has a ratio of 43%:57% based on dry matter. The resulting data were analyzed by Duncan's test. The results showed that MLCP in replacing concentrate had a significant effect (P